Evaluation Of Cold Chain Awareness And Technology Adoption In Cold Chain Operations: A Descriptive Analysis - Imam Jaelani; Budi Harsanto; Yudi Azis; Diana Sari (UNIVED Press, 2025)
The cold chain is a critical logistics system for maintaining the quality of temperature-sensitive products such as food, pharmaceuticals, and vaccines. This study aims to evaluate industry players’ awareness of the importance of cold chain and the level of technology adoption in cold chain operations. A quantitative survey method was used, distributing questionnaires to 150 respondents involved in the cold product supply chain across various sectors. The findings indicate that while 85% of respondents understand the importance of cold chain, only 60% have adopted modern technologies such as digital temperature sensors, IoT, and real-time tracking systems. The main barriers to adoption are investment costs and lack of technical training. This study highlights the importance of awareness programs, training, and incentives to encourage businesses to enhance the efficiency and reliability of the cold chain system in Indonesia. The implications of this research are expected to support the development of policies and strategies for wider implementation of technology in refrigerated logistics systems.